Effects of Herbal Medicine Use on Adherence to Conventional Anticancer Drugs - Karungi, Christine; Asiimwe, Philip; Ssentongo, Conrad; Tuhaise, Sharon Primah; Oloro, Joseph (European Journal of Medicinal Plants, 2020)
Background: Use of herbal medicines alongside conventional anticancer drugs is common among cancer patients. This may potentially cause reduced adherence to conventional anti-cancer drugs, unpredictable side effects and unknown drug-herb interactions. This in the long run could result in poor clinical outcomes. Aim: This study was conducted to investigate how use of herbal medicines affects adherence to conventional anti-cancer drugs, to determine the proportion of patients using both conventional and herbal anticancer medicines and to identify the common herbal medicines used alongside conventional anti-cancer drugs by patients at the Mbarara Regional Referral Hospital Oncology unit. Methods and Findings: A cross-sectional study was conducted in the oncology clinic of Mbarara Regional Referral Hospital found in Mbarara district, Uganda. Data was collected between 20th March and 20th April 2019 from 122 participants who met the inclusion criteria with subsequent consenting. Our primary outcome was adherence and secondary outcome was to investigate whether cancer patients use herbal medicines alongside conventional anti-cancer drugs. Our study had 122 patients most of them belonging to the Banyankole tribe, 75 (61.5%) being males. Of the 72 (59.02%) patients who used herbal medicine, 40 (55.56%) were males and 66.67% of the herbal users reported relief from herbal medicines. Aloe Vera was the most commonly used herb. Most of the patients 77 (63.1%) showed high adherence, this was greater in the non-herbal users than in the herbal users (COR=1.62) though this was not significant (p=0.399). Conclusion: It is most likely that majority of cancer patients use at least one herb during their course of life. The results did not show a significant relationship between herbal medicine use and adherence to conventional anti-cancer drugs. The high proportion of herbal medicine users calls for more research into the area to provide further information that can help optimize cancer treatment outcomes.
Keywords: Cancer; Herbal medicine; Adherence; Anticancer drugs